Portfolio-Based Assessment in English Language Learning: Highlighting the Students’ Perceptions - Ahmad Syamsul Ma'arif; Fuad Abdullah; Asri Siti Fatimah; Arini Nurul Hidayati (UIR Press, 2021)
Portfolio-based Assessment (hereafter, PBA) plays an indispensable role in language assessment. PBA represents the development of the students’ learning process outcomes, trains autonomous learning, and stimulates metacognitive awareness. Conversely, a few investigative attempts, addressed the students’ perceptions of PBA in the Indonesian EFL Context. Therefore, this study aimed to decipher the perceptions of EFL students in Indonesia on PBA use in the English subject. Empirically speaking, two female students were involved as the participants in this study. The data were collected through a semi-structured interview and analyzed with Thematic Analysis (TA) (Braun & Clarke, 2006). The findings revealed that students articulated their perceptions in three major themes, namely developing self-monitoring from the students’ learning processes, generating discipline, responsible and autonomous language learning attitudes, and mitigating perceptual mismatches among teachers and students. Pedagogically speaking, this study indicates that PBA employment can provide opportunities for students to monitor their learning progress, and enhance their self-confidence and learning motivation.